2015
DOI: 10.1093/pcp/pcv089
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellin Promotes Shoot Branching in the Perennial Woody PlantJatropha curcas

Abstract: Strigolactone (SL), auxin and cytokinin (CK) interact to regulate shoot branching. CK has long been considered to be the only key phytohormone to promote lateral bud outgrowth. Here we report that gibberellin also acts as a positive regulator in the control of shoot branching in the woody plant Jatropha curcas. We show that gibberellin and CK synergistically promote lateral bud outgrowth, and that both hormones influence the expression of putative branching regulators, J. curcas BRANCHED1 and BRANCHED2, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
92
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(112 citation statements)
references
References 57 publications
(71 reference statements)
7
92
0
1
Order By: Relevance
“…The importance of GA levels in AXBs themselves is demonstrated by the up-regulation of GA biosynthesis genes in AXBs of hybrid aspen that are released from dormancy by chilling (Rinne et al , 2011). In support of this, GA supply also induces branching in a number of woody species (Saure, 1985; Rinne et al , 2011; Ni et al , 2015). AXBs of hybrid aspen resemble short day (SD)-induced terminal buds (TBs), both morphologically and molecularly (Rinne et al , 2015), although their vascularization might initially differ (Pizzolato and Larson, 1977).…”
Section: Introductionmentioning
confidence: 80%
“…The importance of GA levels in AXBs themselves is demonstrated by the up-regulation of GA biosynthesis genes in AXBs of hybrid aspen that are released from dormancy by chilling (Rinne et al , 2011). In support of this, GA supply also induces branching in a number of woody species (Saure, 1985; Rinne et al , 2011; Ni et al , 2015). AXBs of hybrid aspen resemble short day (SD)-induced terminal buds (TBs), both morphologically and molecularly (Rinne et al , 2015), although their vascularization might initially differ (Pizzolato and Larson, 1977).…”
Section: Introductionmentioning
confidence: 80%
“…Here, we demonstrate that tomato SlGRAS24 is a key transcription factor for coordinated regulation of GA and auxin signalling pathways, which may provide clues to the mechanisms underlying the significantly increased height of Atham1, 2, 3 mutant plants and their shorter primary roots (Engstrom et al ., ; Wang et al ., ). Atham1, 2, 3 mutant plants also have altered lateral branch formation (Schulze et al ., ; Wang et al ., ), a process which is also regulated by auxin and GA (Martínez‐Bello et al ., ; Müller and Leyser, ; Ni et al ., ). Recently, it was found that overexpression of a sunflower ( Helianthus annuus L.) GRAS‐ like gene altered the GA content and axillary meristem outgrowth of transgenic Arabidopsis plants (Fambrini et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…However, how the DELLA-SPL9 complex performs different functions on different target genes remains to be elucidated. Ni et al showed that gibberellin is a positive regulator in controlling axillary bud outgrowth in the perennial woody plant Jatropha curcas (Ni et al 2015). In strawberry, when FveGA20ox4 is mutated, axillary meristems are still dormant, the number of inflorescences is increased in the plant, and GA biosynthesis in the axillary meristem is necessary for inducing stolon differentiation (Tenreira et al 2017).…”
Section: Discussionmentioning
confidence: 99%